Keseimbangan Kewenangan Pemeriksaan Pajak pada Relasi Kewenangan Fiskus dan Perlindungan Hak Wajib Pajak di Indonesia - triyanto triyanto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The authority of tax auditors and taxpayers' rights in the tax reporting process are in conflict in their implementation in the field. This authority extends from tax auditors' authority to conduct audits, issuing tax assessments, and ultimately to the collection process (including blocking and seizure), compared to taxpayers' rights to provide evidence for the tax auditor's determination, even under the selfassessment system. This study aims to analyze the application of the principle of balance between tax auditor authority and taxpayer rights in tax law enforcement in Indonesia, using normative methods using statutory and conceptual approaches. The results indicate that tax auditor authority in the self-assessment system holds a strategic position in overseeing tax compliance. However, its implementation must be limited by the principles of legality, proportionality and accountability to protect taxpayers' rights. This is achieved through the principle of equality before the law and the theory of legal protection. To prevent abuse of authority by tax officials, regulatory strengthening, audit transparency and optimization of legal protection for taxpayers are needed.